The empty city - Hunter, Erin (Hunter, Erin. Survivors, 2013)
Golden-haired mutt Lucky is a Lone Dog, roaming freely while other dogs have Packs. When the Big Growl strikes, the land splits, and suddenly Lucky is forced to search harder for food and clean water. In a desolate world, Lucky teams up with his littermate Bella, and forms a pack of his own in order to survive in the new, dark world.